NORMING DECODING OF BCH CODES WITH THE FIRST ZERO COMPONENTS OF THE SYNDROME - D. N. Hoang; V. K. Konopelko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The present work is dedicated to development of the method of syndrome norms compression by setting to zero the first component of the syndrome. Research is presented for BCH codes of length n = 31 and error-correcting multiplicity t = 4;5;6.